Fluoromycobacteriophages Can Detect Viable Mycobacterium tuberculosis and Determine Phenotypic Rifampicin Resistance in 3–5 Days From Sputum Collection - Rondón, Liliana; Urdániz, Estefanía; Latini, Cecilia; Payaslian, Florencia; Matteo, Mario; Sosa, Ezequiel J.; Do Porto, Darío F.; Turjanski, Adrian G.; Nemirovsky, Sergio; Hatfull, Graham F.; Poggi, Susana; Piuri, Mariana (Frontiers in Microbiology, 2018)
The World Health Organization (WHO) estimates that 40% of tuberculosis (TB) cases are not diagnosed and treated correctly. Even though there are several diagnostic tests available in the market, rapid, easy, inexpensive detection, and drug susceptibility testing (DST) of Mycobacterium tuberculosis is still of critical importance specially in low and middle-income countries with high incidence of the disease. In this work, we have developed a microscopy-based methodology using the reporter mycobacteriophage mCherrybombϕ for detection of Mycobacterium spp. and phenotypic determination of rifampicin resistance within just days from sputum sample collection. Fluoromycobacteriophage methodology is compatible with regularly used protocols in clinical laboratories for TB diagnosis and paraformaldehyde fixation after infection reduces biohazard risks with sample analysis by fluorescence microscopy. We have also set up conditions for discrimination between M. tuberculosis complex (MTBC) and non-tuberculous mycobacteria (NTM) strains by addition of p-nitrobenzoic acid (PNB) during the assay. Using clinical isolates of pre-XDR and XDR-TB strains from this study, we tested mCherrybombΦ for extended DST and we compared the antibiotic resistance profile with those predicted by whole genome sequencing. Our results emphasize the utility of a phenotypic test for M. tuberculosis extended DST. The many attributes of mCherrybombΦ suggests this could be a useful component of clinical microbiological laboratories for TB diagnosis and since only viable cells are detected this could be a useful tool for monitoring patient response to treatment.